(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
This article aims to describe a set of photographic meetings performed between 2013 and 2021, in face-to-face and online formats, about fashion photographic narratives. It is understood that the fashion editorial is a photographic narrative that codifies a fashion theme and brings it closer to the public. It uses as methodology a descriptive and exploratory investigation, of the bibliographic type, and a participant research based on case studies. The main purpose is to understand how the artist finds his own singularity in the shared photographic experience. Joan Fontcuberta (2010), Nicolas Bourriaud (2009) and Berger (2017) are some of the authors studied and who are interested in the shared experience as a complement to the artistic work. It is possible that the artist exhibits a transitive exchange between himself, the photographed and the spectator, and it is considered that the dialogue between the artist and the spectator cannot be shortened without measuring a infinity of other negotiations that take place during the creative process. The collective photographic experience with the potential to make the viewer participate in the narrative involves the binomial of exchange.